The influence of the economic disparities between regions on political polarisation in the Czech Republic - Ondřej Rolník (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2023)
This paper aims to evaluate how the economic prosperity of regions affects the polarization of political representation, and thus of society. It examines whether economically prosperous regions, represented by economic well-being, show lower political polarisation, and whether regions with lower levels of economic prosperity are more likely to elect polarised and extreme political representatives. The paper focuses on the period from the establishment of the Czech Republic in 1993, to the last elections in 2021 in the NUTS 3 regions of the Czech Republic. Evidence was provided through a determination of the effect of economic well-being, defined by three indicators, i.e., gross domestic product per capita, unemployment, and disposable income per capita, on the development of a created political polarisation index. This index is based on the left-right ideological party division combined with election results for the Chambers of Deputies of the Parliament of the Czech Republic of regional districts. Sociodemographic indicators of the development of the individual regions were used as control variables. These include the average population, share of the university-educated population, age indicators, population density of a given region, voter turnout in a specific election year, and various positions in the institutional setting of the Czech Republic. The most significant components of economic well-being that influence the development of polarisation are the growth of disposable income and unemployment. This is demonstrated through a quantitative economic analysis of the panel dataset using the least squares with fixed effects method that uses time-fixed and region-fixed effects.
Keywords: D72; E61; I31; P16; 330; Czech Republic; Polarisation; Politics; Economic Well-Being; Political Economics; Disposable Income